2010
DOI: 10.1007/s00107-010-0425-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of wax emulsions for improvement of wood durability and sorption properties

Abstract: To cite this version:Boštjan Lesar, Miha Humar. Use of wax emulsions for improvement of wood durability and sorption properties. European Journal of Wood and Wood Products, Springer Verlag, 2010, pp.231-238 Waxes are used for treatment of wood surfaces for several decades predominately as surface treatments because they weakly penetrate into the wood. In order to overcome this issue, water emulsions were applied in the present experiment. Five water emulsions of various concentrations were used, namely montan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 7 publications
3
32
0
Order By: Relevance
“…Predominantly, changes to the peak assigned to lignin (1593 cm −1 ) were less noticeable in the presence of wax. This result confirmed that wax emulsions slow wood degradation (Lesar and Humar 2011), which is also evident from the mass losses (Table 3).…”
Section: Ftir Analysissupporting
confidence: 83%
“…Predominantly, changes to the peak assigned to lignin (1593 cm −1 ) were less noticeable in the presence of wax. This result confirmed that wax emulsions slow wood degradation (Lesar and Humar 2011), which is also evident from the mass losses (Table 3).…”
Section: Ftir Analysissupporting
confidence: 83%
“…Wood species and composition of preservative solution did not have signifi cant infl uence on the uptake. This is rather surprising, as the uptake of a viscous solution is usually higher with beech specimens than the uptake with spruce specimens (Lesar and Humar, 2010). Presumably, there are two main reasons for comparable uptakes of beech and spruce wood specimens: fi rstly, the specimens were rather small, with rather high portions of axial surfaces and secondly, the liquefi ed wood contained ethylene glycol that causes wood swelling (Mantanis et al 1994), which enables penetration of larger molecules of liquefi ed wood to less permeable wood species (such as spruce).…”
Section: Rezultati I Raspravamentioning
confidence: 98%
“…Amongst different approaches, the addition of hydrophobic substances in order to hinder the access to water enhancing the durability of wood especially against fungal agents is one of the most suited solutions. Wood protection can be improved by the use of oil and waxes (Treu et al 2004;Lesar and Humar 2011), as well as tall oil, a secondary product of the pulp and paper industry (Hyvönen et al 2006), or pyrolysis fractions (Temiz et al 2010;Palanti et al 2011;Mazela 2007). Other alternative solutions based on lactic acid and proteins were also studied with promising results (Nöel et al 2009a,b;Thevenon et al 1997;Thévenon and Pizzi 2003;Polus-Ratajczak and Mazela 2004).…”
Section: Introductionmentioning
confidence: 99%